2011
DOI: 10.1109/tuffc.2011.2059
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ultrasound tooth imaging using fractional fourier transform

Abstract: Abstract-An ultrasound contact imaging method is proposed to measure the enamel thickness in human tooth. A delay-line transducer with a working frequency of 15 MHz is chosen to achieve a minimum resolvable distance of 400 µm in human enamel. To confirm the contact between the tooth and the transducer, a verification technique based on the phase shift upon reflection is used. Because of the high attenuation in human teeth, linear frequency modulated chirp excitation and pulse compression are exploited to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…This also means that V marked areas might not necessarily have the same SOS present in T marked areas. Furthermore, anisotropy in teeth has been reported by several studies as a primary obstacle for the utilisation of diagnostic ultrasound in dentistry (Harput et al 2011;Huysmans and Thijssen 2000;Louwerse et al 2004;Slak et al 2011;Tagtekin et al 2005). …”
Section: Sos Measurement In Enamel At V Marked Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…This also means that V marked areas might not necessarily have the same SOS present in T marked areas. Furthermore, anisotropy in teeth has been reported by several studies as a primary obstacle for the utilisation of diagnostic ultrasound in dentistry (Harput et al 2011;Huysmans and Thijssen 2000;Louwerse et al 2004;Slak et al 2011;Tagtekin et al 2005). …”
Section: Sos Measurement In Enamel At V Marked Areasmentioning
confidence: 99%
“…Tagtekin et al (2005) investigated ultrasound for monitoring occlusal enamel on worn molars in vitro and concluded that ultrasound was a promising tool for that task. Indeed, several studies have compared ultrasound measurements with histology, the gold standard in the field, but with mixed results (Harput et al 2011;Louwerse et al 2004;Slak et al 2011;Tagtekin et al 2005). One factor that may explain the variation between these studies is the assumed SOS in enamel.…”
Section: Introductionmentioning
confidence: 99%
“…LFM signals and matched filtering techniques are commonly used in a wide range of applications to improve SNR of the received signals such as in [11] and [12]. An LFM signal can be expressed for time t as…”
Section: Lfm Excitationmentioning
confidence: 99%
“…However, the usage of coded excitation in echodentography is not common except some recent studies [6], [7]. In this work, an LFM chirp is used as an excitation signal to improve the signal-to-noise ratio (SNR) and penetration depth.…”
Section: A Coded Excitationmentioning
confidence: 99%
“…The received ultrasound echoes from the tooth sample were saved by a Waverunner 64xi Oscilloscope (LeCroy Corp.) and signals were processed in Matlab (Mathworks Inc.). The contact mode imaging and the importance of glycerin couplant is explained in [7].…”
Section: A Experimental Setupmentioning
confidence: 99%